2017
DOI: 10.1002/ange.201708231
|View full text |Cite
|
Sign up to set email alerts
|

CsB4O6F: A Congruent‐Melting Deep‐Ultraviolet Nonlinear Optical Material by Combining Superior Functional Units

Abstract: The discovery of new nonlinear optical (NLO) materials for coherent light generation in the deep‐ultraviolet (DUV, wavelength below 200 nm) region is essential for the development of laser technologies. Herein, we report a new material CsB4O6F (CBF), which combines the superior structural properties of two well‐known NLO materials, β‐BaB2O4 (BBO) and KBe2BO3F2 (KBBF). CBF exhibits excellent DUV optical properties including a short cutoff edge (155 nm), a large SHG response (≈1.9×KDP), and a suitable birefringe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 175 publications
(55 citation statements)
references
References 46 publications
3
44
0
8
Order By: Relevance
“…Thus, ABF with high performance has significant advantages over KBBF and corresponds to a new type of deep-UV NLO crystal, clearly demonstrating that fluorooxoborates are a new developing source for deep-UV NLO crystals. Subsequently, a new member of the fluorooxoborates, CsB 4 O 6 F (CBF), [54] was designed and obtained based on ABF, and the congruent-melting behavior of CBF ensures the successful replacement of NH 4…”
Section: )mentioning
confidence: 99%
“…Thus, ABF with high performance has significant advantages over KBBF and corresponds to a new type of deep-UV NLO crystal, clearly demonstrating that fluorooxoborates are a new developing source for deep-UV NLO crystals. Subsequently, a new member of the fluorooxoborates, CsB 4 O 6 F (CBF), [54] was designed and obtained based on ABF, and the congruent-melting behavior of CBF ensures the successful replacement of NH 4…”
Section: )mentioning
confidence: 99%
“…Große ABF-Kristalle [53] hoher Qualität ermçglichten optische Charakterisierungen, und es wurden drei zentrale Eigenschaften (Absorptionskanten, Nichtlinearitätskoeffizienten und kürzeste PM-SHG-Wellenlängen) erhalten: 1) Das Transmissionsspektrum im tiefen UV zeigt, dass die Absorptionskante von ABF etwa 156 nm beträgt (Abbildung 7 a), ähnlich der von KBBF (147 nm). In der Folge wurde in Anlehnung an ABF ein neues Mitglied der Fluoroxoborate, CsB 4 O 6 F (CBF), [54] Darüber hinaus wurden neue Mitglieder der Alkalimetallfluoroxoboratfamilie -NaB 4 O 6 F, [55] RbB 4 O 6 F, [56] CsKB 8 O 12 F 2 [56] und CsRbB 8 O 12 F 2 [56] -nacheinander durch Kationensteuerung synthetisiert. Berücksichtigt man auch ABF und CBF, kann die chemische Formel dieser Familie mit AB 4 O 6 F (A = NH 4 , Na, Rb, Cs, K/Cs, Rb/Cs) wiedergegeben werden.…”
Section: Methodsunclassified
“…They made a series of innovative achievements such as photocatalytic water splitting for hydrogen (H 2 ) evolution, 25 selective photoreduction of CO 2 into CO, 26 molecular oxygen activation and RhB degradation. 27,28 Xiao et al 29,30 have successfully synthesized Bi 4 O 5 I 2 nanoakes, which had better photocatalytic activities in the degradation of 4-tert-butylphenol, and predicted that they could be applied to other elds as well.…”
Section: Introductionmentioning
confidence: 99%
“…In general, noncentrosymmetric crystal structure materials may possess very good NLO properties. 28 In 2014, Fan et al [38][39][40] found a series of materials, such as K 3 B 6 O 10 Br, Na 3 VO 2 B 6 O 11 , and M 2 B 5 O 9 Cl (M ¼ Ca, Sr, Ba, Pb), with noncentrosymmetric structures. Due to intrinsic large polarization effects, they not only have good nonlinear optical properties, but have also been found to exhibit signicantly enhanced photocatalytic activities.…”
Section: Introductionmentioning
confidence: 99%